Financial sector restructuring in Greece: The impact on activities, financial health and employment - Loizos, Konstantinos; Missos, Vlassis (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2022)
Developments in the financial sector of the economy has attracted the interest of research community, especially after the crisis of 2008, both in Greece and worldwide. Policy makers in the European Union and elsewhere have played a more active role in shaping the regulatory framework for financial institutions’ operation. In this conjuncture, the Greek financial sector, given its major Non-Performing Loans (NPLs) problem, which has been the outcome of the protracted economic crisis (2009-2016), is passing through a period of restructuring and reconsideration of its business model. This paper reviews the developments concerning key indicators of Greek financial institutions about their activities, employment and financial soundness. Our findings indicate that the economic crisis had a significant impact on the current banking landscape and the business model of financial intermediaries which has been characterized by the deep scars of economic recession.